Postactivation potentiation: Sometimes more fatigue than potentiation. - Koziris, L. (Strength and Conditioning Journal, 2012)
Certain plyometric and isometric protocols failed to produce a postactivation potentiation in vertical jump and bench press throw power output. The isometric protocol in particular, negatively affected the strongest male fencers. Nonetheless, the results can be useful in guiding the practitioner toward experimentation with postactivation potentiation protocols for other athletes.